2009
DOI: 10.1029/2008jb005890
|View full text |Cite
|
Sign up to set email alerts
|

Seismic wave attenuation in carbonates

Abstract: [1] The effect of pore fluids on seismic wave attenuation in carbonate rocks is important for interpreting remote sensing observations of carbonate reservoirs undergoing enhanced oil recovery. Here we measure the elastic moduli and attenuation in the laboratory for five carbonate samples with 20% to 30% porosity and permeability between 0.03 and 58.1 mdarcy. Contrary to most observations in sandstones, bulk compressibility losses dominate over shear wave losses for dry samples and samples fully saturated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(113 citation statements)
references
References 49 publications
4
101
0
Order By: Relevance
“…P-wave amplitude anisotropy is more difficult to measure than velocity anisotropy, but it is shown here to be stronger than velocity anisotropy. In it lies a growing realization that amplitude information has strong potential in understanding the subsurface (Adam et al, 2009), even though reliable amplitude information is typically harder to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…P-wave amplitude anisotropy is more difficult to measure than velocity anisotropy, but it is shown here to be stronger than velocity anisotropy. In it lies a growing realization that amplitude information has strong potential in understanding the subsurface (Adam et al, 2009), even though reliable amplitude information is typically harder to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…When these methods are applied to surface seismic data, with a much lower S/N than that in VSP data, only limited success would be expected (Dasgupta and Clark, 1998). Nevertheless, fit-forpurpose Q values are used routinely for lithological interpretation (Adam et al, 2009;Reine et al, 2009Reine et al, , 2012. The review papers by Campbell et al (2005) and Kaderali et al (2007) amply demonstrate the capacity of VSPs to deliver satisfactory results in an appropriate circumstance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical and experimental studies (e.g., Winkler and Nur, 1982;Akbar et al, 1993;Batzle et al, 2006;Adam et al, 2009) revealed a very strong sensitivity of the seismic waves to pore fluid properties in reservoir rocks. All of these papers conclude that seismic data have a great potential in determining these key physical parameters.…”
Section: Introductionmentioning
confidence: 99%